Comorbidity of periodontal disease: two sides of the same coin? An introduction for the clinician. Issue 1 (1st January 2017) - Holmstrup, Palle; Damgaard, Christian; Olsen, Ingar; Klinge, Björn; Flyvbjerg, Allan; Nielsen, Claus Henrik; Hansen, Peter Riis
ABSTRACT: Increasing evidence has suggested an independent association between periodontitis and a range of comorbidities, for example cardiovascular disease, type 2 diabetes, rheumatoid arthritis, osteoporosis, Parkinson's disease, Alzheimer's disease, psoriasis, and respiratory infections. Shared inflammatory pathways are likely to contribute to this association, but distinct causal mechanisms remain to be defined. Some of these comorbid conditions may improve by periodontal treatment, and a bidirectional relationship may exist, where, for example, treatment of diabetes can improve periodontal status. The present article presents an overview of the evidence linking periodontitis with selected systemic diseases and calls for increased cooperation between dentists and medical doctors to provide optimal screening, treatment, and prevention of both periodontitis and its comorbidities.